Fixed point theorems for F- contraction mapping in complete rectangular M-metric space - Mohammad Asim; Samad Mujahid; Izhar Uddin (Applied General Topology, 2022)
In this paper, we prove a fixed point result for F- contraction principle in the framework of rectangular M-metric space. An example is also adopted to exhibit the utility of our result. Finally, we apply our fixed point result to show the existence of solution of Fredholm integral equation.